As feiras de ciências em Abaetetuba-PA - SENA, Maria do Socorro Lobo (2024)
The present work described the perception of teachers and students about the Science Fairs in the municipality of Abaetetuba-PA. A questionnaire was prepared semi-structured and interview with teachers and students was carried out. It was verified that during the science fair, elementary and high school students develop experiments that promote socialization, the exchange of teaching-learning-knowledge experiences with the community. In this way it makes possible a expansion of the world view of participants, exhibitors and visitors to the Fair.During the event, there is an increase in the dissemination of research through the exchange of experiences among the participants. In this sense, the teacher is the guiding and encouraging the students, and the students are the facilitating agents of the knowledge to the community.